Ameliorative Effect Of Herbomineral Toxin Binder ‘vilocym’ On Mycotoxicosis In Broilers - Sawarkar, A.R.; Sonkusale, P.M.; Thakare, P.D.; Jangade, C.R. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A study was conducted in 75 day old Vencobb broiler chicks to evaluate toxic effects of aflatoxin B1 and ochratoxin A and efficacy of herbomineral toxin binder product (Vilocym) in preventing co mycotoxicosis. Supplementation of herbomineral toxin binder feed supplement (Vilocym) helps in amelioration of toxic effects produced during mixed mycotoxicosis in broilers.
Keywords: Aflatoxicosis; ochratoxicosis; broiler; performance; herbo-mineral toxin-binder